Access to psychosocial support for church-going young people recovering from drug and substance abuse in Zimbabwe: a qualitative study - Faustina F. Muswerakuenda; Paddington T. Mundagowa; Clara Madziwa; Fadzai Mukora-Mutseyekwa (BMC, 2023)
Abstract Background The church and other religious-affiliated organizations have promising yet underexplored potential to provide social support services for young people recovering from substance abuse in communities where drug and substance rehabilitation services are limited. This study aimed to establish the barriers and facilitators of accessing psychosocial support, the role of the church, and strategies to promote access to psychosocial support for youths recovering from drug and substance abuse. Methods This was a qualitative cross-sectional study, and semi-structured interviews of 18 church-going youths and three youth pastors were conducted in eastern Zimbabwe. Data were collected using recorded telephone interviews. Data were transcribed and analyzed using the thematic network analysis technique of producing basic themes, which build into organizing themes. Organizing themes produces one overarching global theme. The Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines for reporting on qualitative research were used in reporting the study findings. Results The interviews produced the following basic themes under organizing theme barriers: stigma and discrimination, parental/guardian denial, radical religious beliefs, and negative role models. Under the organizing theme facilitators, the basic themes were acceptance, confidentiality, peer and parental support, and an organized support program. The church acted as the bridge between the barriers to access to services and support seeking through innovative, inclusive projects and activities, as well as a pillar of social support. Conclusions Acceptance of one's addiction problem is critical to initiate seeking psychosocial support. Confidentiality, support from trustworthy relationships, and the availability of a well-coordinated recovery program enable young people to seek support. We recommend formal training church-based counselors in the ethical aspects of psychotherapy to reduce the preconceived social stigma associated with drug and substance abuse.